Life Cycle Cost Analysis of a Standalone PV System - Abdul Qayoom, Jakhrani; Othman, A.K.; Andrew Ragai, Henry Rigit; Saleem, Raza Samo; Shakeel Ahmed, Kamboh (IEEE, 2011)
The purpose of this paper is to assess the viability of standalone photovoltaic (SAPV) systems for the supply of electricity in remote areas of Sarawak. In order to achieve the objectives, the life cycle cost (LCC) of a SAPV system was computed by means of net present value (NPV) technique. All anticipated costs were discounted to their present values by considering the time value of money. It was found that the capital cost makes up around 58% and future costs shares 42% of all expenses. PV modules contribute 9% and battery bank shares 52% with almost 8 days of autonomy at LLP of 0.01. Controller adds 5%, inverter 8%, civil work 17% and O&M 9% of total life time system cost. The estimated net energy cost from SAPV system was found to be US$2.5/kWh, which is 20 times higher than average electricity tariff in Malaysia. It is concluded that the SAPV systems could only be preferred where the extension of power transmission lines is expensive for the supply of electricity in isolated areas.